The influence of exposure to foreign literature on Chinese readers’ out-group attitudes: the sequential mediating role of emotional investment and cultural empathy - Qi, Zhi; You, Hong (Frontiers in Psychology, 2025)
IntroductionThis study examines the impact of exposure to foreign literature on out-group attitudes among Chinese readers.MethodsA sequential mediation model is tested, and the effect of exposure to foreign literature on out-group attitudes is mediated by emotional investment and cultural empathy. The study included 799 Chinese readers of foreign literature. Participants’ ages ranged from 19 to 48 years, with a mean age of 34.72 (SD = 5.03). Using a sequential mediation model, we explored how foreign literature might indirectly shape attitudes toward diverse social groups through heightened emotional and empathetic engagement.ResultsThe exposure to foreign literature significantly predicts positive out-group attitudes, both directly and indirectly. Specifically, emotional investment in foreign narratives facilitates a personal connection to characters from different backgrounds, enhancing cultural empathy and, in turn, more favorable out-group attitudes.DiscussionOur findings highlight that foreign literature is a valuable medium for fostering intercultural empathy by providing readers with indirect experiences of diverse cultural perspectives. Additionally, the study underscores the importance of carefully curated literary selections and structured educational approaches to maximize the positive impact of foreign literature on readers’ attitudes. These results contribute to understanding literature’s role in promoting inclusivity, with implications for educational practices that foster empathy and reduce prejudice. Future research should continue to investigate the specific genres, themes, and teaching techniques that most effectively cultivate cultural empathy and open-mindedness in an increasingly globalized society.